(untitled) (Journal of Enam Medical College, 2015)
Ebola virus is a filamentous, enveloped, non-segmented, single-stranded, negative-sense RNA virus. It belongs to the Filoviridae and was first recognized near the Ebola River valley in Zaire in 1976. Since then most of the outbreaks have occurred to both human and nonhuman primates in sub-Saharan Africa. Ebola virus causes highly fatal hemorrhagic fever in human and nonhuman primates. In addition to hemorrhagic fever, it could be used as a bioterrorism agent. Although its natural reservoir is yet to be proven, current data suggest that fruit bats are the possibility. Infection has also been documented through the handling of infected chimpanzees, gorillas, monkeys, forest antelope and porcupines. Human infection is caused through close contact with the blood, secretion, organ or other body fluids of infected animal. Human-to-human transmission is also possible. Ebola virus infections are characterized by immune suppression and a systemic inflammatory response that causes impairment of the vascular, coagulation, and immune systems, leading to multiorgan failure and shock. The virus constitutes an important public health threat in Africa and also worldwide as no effective treatment or vaccine is available till now DOI: http://dx.doi.org/10.3329/jemc.v5i1.21497 J Enam Med Col 2015; 5(1): 44-51